DETERMINAN DEFISIT NERACA TRANSAKSI BERJALAN DAN DEFISIT ANGGARAN: TWIN DEFICIT INDONESIA - Chrisna Ludfernando; Edy Yusuf Agung Gunanto (Center for Economic Studies Universitas Katolik Parahyangan, 2023)
The global crisis has pushed Indonesia into external and internal imbalances. In this case, the current account deficit is one of the important issues related to external balance because it is related to Indonesia's foreign exchange reserves. A crisis causes not only external imbalances but also causes internal imbalances. The Indonesian government uses the State Revenue and Expenditure Budget (APBN) as an instrument in achieving internal balance, but Indonesia implements a deficit budget policy so that with this condition Indonesia experiences a twin deficit. This study aims to analyze the determinants that cause a deficit in the current account balance and government budget. The government budget, exchange rate, economic growth, commodity price index, and trade openness variables are used to analyze the current account balance determinants. Meanwhile, to analyze the determinants of the government's budget, the variables of economic growth, inflation, and interest rates are used. The analytical tool used is the Error Correction Model (ECM). The results showed that the variables of economic growth, commodity price index, and trade openness had a significant negative effect on the current account balance in the long and short term. The government budget variable has a significant positive effect in the short term on the current account balance, while the exchange rate variable has a negative and significant effect on the current account balance in the long term. In the determinants of the government budget, the variable of economic growth has a significant positive effect in the long and short term, while the inflation variable has a significant negative effect in the long and short term. However, the interest rate variable has no significant effect in the long and short term.